2011
DOI: 10.1590/s0100-29452011000300029
|View full text |Cite
|
Sign up to set email alerts
|

Fungos micorrízicos arbusculares, bactérias diazotróficas e adubação fosfatada em mudas de mamoeiro

Abstract: RESUMO-Conduziu-se um experimento em casa de vegetação para avaliar o crescimento de mudas de mamoeiro inoculadas com fungos micorrízicos arbusculares (FMAs) e com bactérias diazotróficas, na ausência e presença de fósforo. O delineamento experimental foi o de blocos casualizados, em arranjo fatorial 4 x 3 x 2, sendo os tratamentos compostos por: espécies de fungos micorrízicos arbusculares Glomus clarum, Gigaspora margarita, o inóculo misto Glomus clarum + Gigaspora margarita e o controle sem FMAs; as bactéri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
1
10
0
7
Order By: Relevance
“…Inoculation with E. colombiana, G. margarita and S. heterogama promoted a 32, 33 and 36% increase in shoot dry matter, respectively, in relation to the control treatment, but did not differ among the fungal species (Table 3). Lima at al. (2011) reported that papaya seedlings inoculated with mycorrhizal fungi exhibited higher growth rates than those not inoculated, regardless of the amount of phosphorus in the soil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inoculation with E. colombiana, G. margarita and S. heterogama promoted a 32, 33 and 36% increase in shoot dry matter, respectively, in relation to the control treatment, but did not differ among the fungal species (Table 3). Lima at al. (2011) reported that papaya seedlings inoculated with mycorrhizal fungi exhibited higher growth rates than those not inoculated, regardless of the amount of phosphorus in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…(2001a) demonstrated that papaya cultivars can benefit from inoculation with Glomus clarum and G. margarita, reducing up to seven times the need for P fertilization so that maximum shoot growth can be achieved. Lima at al. (2011), evaluating growth of papaya cv Golden seedlings, showed that fungal inoculation treatments promoted an increase in seedling leaf area, with an increment of 19.3% in relation to the control treatment, which influenced dry matter accumulation but did not differ among the fungal species studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to the preparation of these seedlings is to use AMFs, which have contributed to reduce the production time of several fruit trees such as citrus (Altoé et al, 2008), yellow passion fruit (Cavalcante et al, 2001;Cavalcante et al, 2002), sweet passion fruit (Anjos et al, 2005;Vitorazi et al, 2012), papaya (Lima et al, 2011) and cashew (Weber et al, 2004), in addition to reducing phosphate fertilization (Riter Netto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Os fungos micorrízicos arbusculares, por sua vez, também têm proporcionado efeitos positivos no crescimento de plantas (Lima et al, 2011;Coelho et al, 2012), além do aumento da absorção de nutrientes, como o fósforo (Santos et al, 2011a) e o nitrogênio (Santos et al, 2011b). Assim, a utilização desses insumos pode promover um crescimento maior das mudas e, consequentemente, reduzir a fase de viveiro.…”
Section: Introductionunclassified